2021
DOI: 10.1007/s11605-021-05045-7
|View full text |Cite
|
Sign up to set email alerts
|

Revisional Adjustable Gastric Band in Roux-en-Y Gastric Bypass—Is It Worth It?

Abstract: Purpose A subset of patients undergoing Roux-en-Y gastric bypass (RYGB) presents with either insufficient weight loss or weight regain. Data on the revisional restrictive options including laparoscopic adjustable gastric band (LAGB) is scarce. This study analyzes the mid-term efficacy and safety of LAGB as a revisional procedure after RYGB. Methods Data of all patients with revisional LAGB after primary RYGB between January 2011 and May 2019 were retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…These results are consistent with previous evidence on EWL outcomes with this salvage procedure. 10 17 Importantly, there is paucity of data on long-term outcomes with LAGB after failed RYGB. Median/mean follow-up in previous studies ranges from 14 months to 33.5 months.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These results are consistent with previous evidence on EWL outcomes with this salvage procedure. 10 17 Importantly, there is paucity of data on long-term outcomes with LAGB after failed RYGB. Median/mean follow-up in previous studies ranges from 14 months to 33.5 months.…”
Section: Discussionmentioning
confidence: 99%
“…Median/mean follow-up in previous studies ranges from 14 months to 33.5 months. 10 17 Liu et al followed 20 patients (out of 86 study participants) for 5 years and reported a 65.9% EWL. 15 The series with the longest overall follow-up (33.5 months) by Lazardis et al reported a 37.6% EWL, which is comparable to our EWL outcomes at 4 years of 28.2%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations